Signal Factors Secreted by 2D and Spheroid Mesenchymal Stem Cells and by Cocultures of Mesenchymal Stem Cells Derived Microvesicles and Retinal Photoreceptor Neurons - Lili Xie; Mao Mao; Liang Zhou; Lusi Zhang; Bing Jiang (Stem Cells International)
We aim to identify levels of signal factors secreted by MSCs cultured in 2D monolayers (2D-MSCs), spheroids (spheroids MSCs), and cocultures of microvesicles (MVs) derived from 2D-MSCs or spheroid MSCs and retinal photoreceptor neurons. We seeded 2D-MSCs, spheroid MSCs, and cells derived from spheroids MSCs at equal numbers. MVs isolated from all 3 culture conditions were incubated with 661W cells. Levels of 51 signal factors in conditioned medium from those cultured conditions were quantified with bead-based assay. We found that IL-8, IL-6, and GROα were the top three most abundant signal factors. Moreover, compared to 2D-MSCs, levels of 11 cytokines and IL-2Rα were significantly increased in conditioned medium from spheroid MSCs. Finally, to test if enhanced expression of these factors reflects altered immunomodulating activities, we assessed the effect of 2D-MSC-MVs and 3D-MSC-MVs on CD14+ cell chemoattraction. Compared to 2D-MSC-MVs, 3D-MSC-MVs significantly decreased the chemotactic index of CD14+ cells. Our results suggest that spheroid culture conditions improve the ability of MSCs to selectively secrete signal factors. Moreover, 3D-MSC-MVs also possessed an enhanced capability to promote signal factors secretion compared to 2D-MSC-MVs and may possess enhanced immunomodulating activities and might be a better regenerative therapy for retinal degenerative diseases.